2015
DOI: 10.1002/joc.4510
|View full text |Cite
|
Sign up to set email alerts
|

Trends in extreme temperature over Nigeria from percentile‐based threshold indices

Abstract: This study analyses spatial and temporal trends in extreme temperature indices over Nigeria. The percentile indices were calculated from newly homogenized daily minimum and maximum temperature data for the period 1971-2012 for 21 stations in Nigeria. Indices describing the characteristics of hot extremes and cold extremes are calculated with the RClimDex software. The annual and seasonal trends in these indices are obtained using the ordinary least square fit and the statistical significance tested using the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 50 publications
6
53
1
Order By: Relevance
“…The precipitation indices, consisting of annual total precipitation, number of wet days, monthly maximum 1-day precipitation, monthly maximum consecutive 5-day precipitation, annual number of days when precipitation is greater than 10 mm, annual number of days when precipitation is greater than 20 mm increased while consecutive wet days decreased. These findings correspond with other observed climate extremes reported in similar studies [38,[45][46][47]. The use of renewable energy tools to reduce the amount of greenhouse gases in the atmosphere and a means of dissipating water bodies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The precipitation indices, consisting of annual total precipitation, number of wet days, monthly maximum 1-day precipitation, monthly maximum consecutive 5-day precipitation, annual number of days when precipitation is greater than 10 mm, annual number of days when precipitation is greater than 20 mm increased while consecutive wet days decreased. These findings correspond with other observed climate extremes reported in similar studies [38,[45][46][47]. The use of renewable energy tools to reduce the amount of greenhouse gases in the atmosphere and a means of dissipating water bodies.…”
Section: Discussionsupporting
confidence: 90%
“…Regional studies have shown similar trends in temperature indices with this study. A general warming trend was found throughout the Guinea, Savanna, and Sahel region of Nigeria from 1971-2012 [45,47,51] as there were more frequent warm nights and days and less cool nights and days. Also the precipitation trend increased but not as significant as temperature indices.…”
Section: Precipitation Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have applied one or a combination of the indices to examine trends in extreme temperature events in different regions of the world including Africa in general, and Nigeria in particular (e.g. Alexander et al, 2006;Fontaine et al, 2013;Kruger and Sekele, 2013;Mackellar et al, 2014;Abatan et al, 2016). These indices have produced robust statistical information.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial and temporal characteristics study of daily temperature extremes over Southern and West Africa show patterns consistent with warming over most of the regions . In Nigeria, Abatan et al (2016) used only percentile-based threshold indices to examine trends in extreme temperature. Their work reported that all the regions in Nigeria were characterized by significant increases in annual frequency of warm days and night, while annual frequency of cold days and nights have similar proportions of significant decreases.…”
Section: Introductionmentioning
confidence: 99%